Vlog Task Based Language Teaching with Youtube Media in The Teaching Speaking for High School - Virdaus, Varia Virdania; Rahmasari, Annisa; Rifa’i, Saiful (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
This study examined the effectiveness of using YouTube as a media tool in conjunction with Vlog Task-Based Language Teaching (TBLT) to improve high school students' speaking abilities. This study used a quasi-experimental desing. While the control group adhered to a traditional curriculum that excluded vlogs and digital media, the experimental group actively participated in Vlog TBLT sessions, where students produced, edited, and engaged with YouTube video content. The findings showed that students' speaking skills significantly improved after being exposed to the Vlog TBLT technique. Compared to the passive learning seen in traditional approaches, the active participation demanded by vlog-based assignments allowed for a more deep and engaged learning experience, producing better results. Additionally, the findings implied that using YouTube vlogs in language instruction not only improved speaking ability but also fostered higher levels of student interest and involvement. This study had important ramifications for teachers looking to integrate digital media into their lesson plans. This study offered a viable substitute for conventional educational approaches that might not be able to satisfy the demands of today's students by demonstrating that Vlog TBLT with YouTube could be a potent instrument in contemporary language instruction. In the end, this study promoted a change to more creative and captivating teaching methods that used technology to improve language learning results.